2016
DOI: 10.1007/s40995-016-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Phenolic Content and Antioxidant Activity of Salvia macrosiphon

Abstract: The use of plants and their products as sources of antioxidants to enhance health and food preservation is currently of great interest. Many plant species, especially those belonging to the Lamiaceae family have exhibited strong antioxidant activity. Salvia macrosiphon is an endemic medicinal plant in Iran, belonging to Lamiaceae family and has many pharmaceutical properties. This study was carried to evaluate the effects of different concentrations of sodium chloride [0.4 (control), 2.3, 4.5 and 6.8 dSm -1 ] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Marathon) and the loss was higher for flavonoids than for sinapic acid derivates [ 117 ]. Furthermore, salinity stress can change the chemical contents of various phenolic compounds in rice cultivars (tolerant and susceptible varieties), causing a large increase in total phenolics and the content of vanillin and protocatechuic acid in tolerant varieties, whereas in contrast, a markedly reduce is found in the susceptible cultivar [ 118 ]. The effect of NaCl concentration on total phenolic content in S. macrosiphon showed that all the treatments with different concentration of NaCl elicited a remarkable reduction of total phenolic content in the leaf which decreased with the treatment of increasing NaCl concentration.…”
Section: Response Of Plant Sms To Soil Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Marathon) and the loss was higher for flavonoids than for sinapic acid derivates [ 117 ]. Furthermore, salinity stress can change the chemical contents of various phenolic compounds in rice cultivars (tolerant and susceptible varieties), causing a large increase in total phenolics and the content of vanillin and protocatechuic acid in tolerant varieties, whereas in contrast, a markedly reduce is found in the susceptible cultivar [ 118 ]. The effect of NaCl concentration on total phenolic content in S. macrosiphon showed that all the treatments with different concentration of NaCl elicited a remarkable reduction of total phenolic content in the leaf which decreased with the treatment of increasing NaCl concentration.…”
Section: Response Of Plant Sms To Soil Salinitymentioning
confidence: 99%
“…The effect of NaCl concentration on total phenolic content in S. macrosiphon showed that all the treatments with different concentration of NaCl elicited a remarkable reduction of total phenolic content in the leaf which decreased with the treatment of increasing NaCl concentration. After induced with 6.8 dS m −1 NaCl, the content of total phenolics was reduced by 2.6 times as compared to control leaves [ 118 ]. However, NaCl salinity increased total antioxidant activity in methanolic extract of the leaf, probably due to the increasing activity of peroxidase (POD) under salt stress conditions [ 119 ].…”
Section: Response Of Plant Sms To Soil Salinitymentioning
confidence: 99%
“…Our result is accordance with the study of Sairam and Saxena (2000); Shao et al (2005) and Chugh et al (2011). Cultivar exhibited a higher CAT activity compared to another found tolerant under drought condition (Valifard et al 2012). …”
Section: Superoxide Dismutase Specific Activitymentioning
confidence: 91%
“…The use of plants with rich phytoconstituents as sources of pharmacological products to enhance health defense is currently of great interest 8 . There has been an exponential growth in study of pharmacological properties of Clitoria ternatea (CT) for its promising future development.…”
Section: Introductionmentioning
confidence: 99%